PERAN DINAS PEMBERDAYAAN MASYARAKAT KAMPUNG DALAM PENYALURAN DANA KAMPUNG DI KABUPATEN PUNCAK JAYA - Yahya Wonorenggo; Akbar Silo (Universitas Cenderawasih, 2022)
This study aims to analyze and determine the role of the Village Community Empowerment Service in Village Fund Distribution in Puncak Jaya Regency, both what factors support and hinder the Village Fund Distribution mechanism. This research is qualitative research with the main objective to describe or describe in detail and depth the role of the Village Community Empowerment Service in overseeing and supervising the process of implementing village fund distribution so that it can contribute as expected by the government for the village community in Puncak Jaya Regency. The data collection technique used is the free guided interview method, observation, and documentation. After the researcher collected the data, the next step was data analysis. The analysis that the researchers carried out used two ways, namely processing the initial data and classifying it, and the next stage the data would be analyzed. The results of this study indicate that: 1) The role of the Village Community Empowerment Service (DPMK) has been effective in distributing the Village Fund Allocation in Puncak Jaya Regency: (a) Obeying the rules and regulations: tupoksi that have been regulated in the Act and Ministerial Regulation. Factors that hinder the performance and role of DPMK are (a) village delays in setting APBDes, (b) whether factors are an obstacle, and (c) problems with changing village apparatus and village human resources. 3). Lack of human resources who do not understand about government management.